2011
DOI: 10.1080/10538712.2011.575445
|View full text |Cite
|
Sign up to set email alerts
|

Child Abuse, Early Maladaptive Schemas, and Risky Sexual Behavior in College Women

Abstract: Previous research suggests that individuals abused as children are more likely to engage in risky sexual behavior during adulthood. The present study examined early maladaptive schemas as mediators of the child abuse-risky sexual behavior relationship among 653 college women. Self-report surveys assessed three forms of child abuse: Sexual, physical, and emotional, and assessed early maladaptive schemas within two domains: Disconnection/rejection and Other-Directedness. Disconnection/rejection schemas fully med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 32 publications
3
34
0
16
Order By: Relevance
“…These associations persist even when the models control for the demographic variables of ever married, never pregnant, religion, and wealth, although the association between childhood sexual violence and multiple partners was of borderline statistical significance. The association between a history of childhood sexual violence and sexual risk-taking behaviors among young adult Tanzanian females is consistent with research that has been done in other geographic and cultural contexts (Bensley et al, 2003; Felitti et al, 1998; Lalor & McElvaney, 2010; Roemmele & Messman-Moore, 2011; Senn & Carey, 2010; Wilson & Widom, 2008). …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These associations persist even when the models control for the demographic variables of ever married, never pregnant, religion, and wealth, although the association between childhood sexual violence and multiple partners was of borderline statistical significance. The association between a history of childhood sexual violence and sexual risk-taking behaviors among young adult Tanzanian females is consistent with research that has been done in other geographic and cultural contexts (Bensley et al, 2003; Felitti et al, 1998; Lalor & McElvaney, 2010; Roemmele & Messman-Moore, 2011; Senn & Carey, 2010; Wilson & Widom, 2008). …”
Section: Discussionsupporting
confidence: 86%
“…In addition to the immediate risks of childhood sexual violence, many studies have established a strong association between experiences of childhood sexual violence and later engagement in sexual risk-taking behaviors such as having multiple sexual partners, inconsistent condom use, and participation in intergenerational and transactional sex (Bensley, Van Eenwyk, & Wynkoop Simmons, 2003Felitti et al, 1998; Lalor & McElvaney, 2010; Roemmele & Messman-Moore, 2011; Senn & Carey, 2010; Wilson & Widom, 2008). Severe or recurrent exposure to stress during childhood, such as sexual violence victimization, can profoundly impact brain circuits and hormonal systems that regulate stress, leading to alterations in the brain architecture and damaged stress regulatory response (Adler & Ostrove, 1999; Herringa et al, 2013; McEwen & Seeman, 1999; National Scientific Council on the Developing Child, 2014).…”
mentioning
confidence: 99%
“…Finally, few studies have examined the link between emotion dysregulation and STI risk among incarcerated women. Other studies exploring emotion management as a mechanism linked to sexual risk have focused on adolescents (Brown et al 2008; DiClemente et al 2001), or college women in relation to HIV (Roemmele and Messman-Moore 2011). Expanding our understanding of emotion dysregulation and STI risk among a high risk population of women such as incarcerated women with histories of interpersonal violence can offer additional insight into this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Substance use has also been found to mediate the association between CSA and risky sexual behaviors (Senn et al, 2008). Roemmele and Messman-Moore (2011) found that early maladaptive schemas 6 including disconnection and rejection, defectiveness/shame, and abandonment schemas were associated with risky sexual behavior among those with histories of CSA and childhood physical abuse. Self-hatred was strongly linked to self-harming (β = .45, p < .001) in a study of 782 adolescents (Xavier et al, 2016).…”
Section: Shame Linked To Revictimization Health Risk Behaviors and mentioning
confidence: 99%